Application of Management Information Systems in Improving Operational Efficiency in Trading Companies - Muhammad Irwan Padli Nasution; M.ikhsan (ISNU Nine-Star Multidisciplinary Journal, 2025)
The development of information technology encourages trading companies to adopt systems that are able to increase the effectiveness and efficiency of operational activities. One of the important instruments in this context is the Management Information System (SIM), which plays a role in processing data into relevant information for managerial decision-making. This study aims to analyze the application of Management Information Systems in improving the operational efficiency of trading companies, especially in the decision-making process, inventory supervision, and data and transaction management. The research method used is qualitative descriptive with a literature study approach, through the review of books, scientific articles, and relevant literature sources that discuss the application of SIM in business operational activities. The results of the study show that the implementation of SIM is able to speed up the transaction process, minimize administrative errors, and improve the accuracy and integration of inventory and financial data. In addition, the driver's license provides convenience in operational supervision and supports faster and more precise decision-making. With an integrated system, companies can increase employee productivity, save work time, and reduce operational costs. In conclusion, the implementation of Management Information Systems has a strategic role in increasing operational efficiency and added value of trading companies in a sustainable manner.